Melhoria da Lingotabilidade do Aço Inoxidável Ferrítico AISI 409 na ArcelorMittal Inox Brasil - Joilson Moreira Ferreira da Silva (2009)
Stainless steels are known for their beauty and corrosion resistance. Ferritic stainless steels, without nickel, are responsible for the increase the consumption of stainless steels in the world, due to the economic advantage as compared to austenitic stainless steels. In the automobile industry, more specific in the cars exhaust system, the use of ferriticstainless steels stabilized with titanium and/or niobium, with low carbon and nitrogen contents and good corrosion resistance, is very common. The AISI 409 steel, corresponding to the P409A steel in the internal ArcelorMittal Inox Brazil normalization, is the most used steel in the exhaust system. During the casting of P409A steels, a frequent problem is the clogging of the submerged entry nozzle. This clogging affects productivity and quality of the steel. In the present work, submerged entry nozzles presenting clogging were analyzed. Titanium (TiO2), aluminum (Al2O3) and magnesium oxides (MgO) were detected in these nozzles. The effects of Ti and Si contents and of the Si/Ti ratio on the occurrenceof nozzle clogging were then investigated. It was determined that Si/Ti ratio inferior than 3.5 significantly reduced nozzle clogging and improved the castability of the P409 steel, without affecting its the microstructure,cleanliness, anisotropy and mechanical properties. The improvement in the castability lead to a reduction in slab grinding index from 43.1 % in 2006 to 27.9 % in 2009 and also in the deviation in cold rolling due to skinlamination from 1.9% in 2006 to 0.5% in 2009